2009
DOI: 10.1016/j.expthermflusci.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer mechanisms in an impinging synthetic jet for a small jet-to-surface spacing

Abstract: Impinging synthetic jets have been identified as a promising technique for cooling miniature surfaces like electronic packages. This study investigates the relation between the convective heat transfer characteristics and the impinging synthetic jet flow structure, for a small jet-to-surface spacing H/D = 2, dimensionless stroke length 1 < L 0 /D < 22, and Reynolds number 1000 < Re < 4300. The heat transfer measurements show evidence for a power law relationship between the Reynolds and Nusselt number for a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 11 publications
10
75
2
1
Order By: Relevance
“…Beyond this distance however the ambient air re-circulates and therefore a significant increase in air temperature is experienced. This is consistent with PIV flow measurements presented by McGuinn et al [22] and Valiorgue et al [10]. This does not occur at larger values of H/D as the slug flow no longer impinges directly on the heated surface.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Beyond this distance however the ambient air re-circulates and therefore a significant increase in air temperature is experienced. This is consistent with PIV flow measurements presented by McGuinn et al [22] and Valiorgue et al [10]. This does not occur at larger values of H/D as the slug flow no longer impinges directly on the heated surface.…”
Section: Resultssupporting
confidence: 91%
“…This does not occur for the synthetic air jet at the lower value of H/D tested but is observed at the higher value of H/D = 6 as indicated in figure 3(a). For similar stroke length, Re = 1020 and H/D = 2, Valiorgue et al [10] show a small secondary peak around r/D = 3, although this study applies a constant wall flux boundary condition. By comparison with particle image velocimetry (PIV) measurements, the peak location coincides with the point where the vortex loses coherence and dissipates into turbulence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Valiorgue et al [8] and Smith and Glezer [9], however only Valiorgue et al [8] It has been shown for impinging continuous jets how turbulent mixing of the flow can enhance heat surface transfer [10]. Since the nature of the synthetic jet flow is highly transient, it is reasonable to infer that its turbulent characteristics may depend not only on Reynolds number, but also on stroke length.…”
Section: Impinging Synthetic Jets For Heat Transfer Applicationsmentioning
confidence: 97%